ANALISIS PROSEDUR PENDATAAN DAN PENILAIAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) PADA BADAN PENDAPATAN DAERAH KABUPATEN BANDUNG - Fadzil Muhammad; Anissa Yuniar Larasati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research aims to analyze the procedures of data collection and valuation for land and building tax of rural and urban areas in Bandung Regency Regional Revenue Agency. This research used a qualitative approach involving 3 informants. Data were collected through interviews, observation, and documentation. The research results show that the PBB-P2 data collection process is in accordance with the regulations, while the PBB-P2 valuation process is still not in accordance with the regulations. To carry out data collection and revaluation of PBB-P2, the Bandung Regency Regional Revenue Agency refers to the same procedures as data collection and valuation of new tax objects. However, data collection and revaluation of PBB-P2 in the form of mass data updates are still difficult to carry out. This activity was carried out partially from 2013 to 2019 through collaboration with third parties. Obstacles that occur during data collection and revaluation of PBB-P2 are lack of budget, rejection and objection from taxpayers, lack of human resources, lack of accuracy of officers, and the absence of valuer of PBB-P2